"Aspects of linguistic contact in Latin votive inscriptions of western provinces: the case of the plural divinities" (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The author proposes the analysis of a group of mixed inscriptions dedicated to plural divinities discovered in provincial contexts of the Western Empire in which it is possible to find aspects of linguistic contact between epichoric languages and Latin. The votive inscriptions belong to advanced stages of the Romanisation process and bear a theonymic formula where it is possible to find two types of epichoric endings: one of Indo-European origin in *-bhos and one of Germanic origin in -ims. The use of epichoric endings in the theonymic formulas was probably due to aspects of conservatism of religious nature.
Keywords: Plural Theonyms; Phenomenon of Linguistic Contacts; Endings in -bos / -ims; Linguistic-Religious Conservatism; Epichoric Languages